Raspberry Pi-Based IoT System for Grouting Void Detection in Tunnel Construction - Weibin Luo; Junxing Zheng; Yu Miao; Lin Gao (Buildings)
This paper presents an IoT-based solution for detecting grouting voids in tunnel construction using the Raspberry Pi microcomputer. Voids between the primary and secondary tunnel linings can compromise structural integrity, and traditional methods like GPR lack continuous feedback. The proposed system uses embedded electrical wires in the secondary lining to measure conductivity, with disruptions indicating unfilled voids. The Raspberry Pi monitors this in real time, uploading data to a cloud platform for engineer access via smartphone. Field tests were conducted in a full-scale, 600 m long tunnel to evaluate the system’s effectiveness. The tests demonstrated the system’s accuracy in detecting voids in various tunnel geometries, including straight sections, curves, and intersections. Using only the proposed void detection system, the largest void detected post-grouting was 1.8 cm, which is within acceptable limits and does not compromise the tunnel’s structural integrity or safety. The system proved to be a cost-effective and scalable solution for real-time monitoring during the grouting process, eliminating the need for continuous manual inspections. This study highlights the potential of IoT-based solutions in smart construction, providing a reliable and practical method for improving tunnel safety and operational efficiency during grouting operations.